What drives compliance? The effect of deterrence and shame emotions on young drivers’ compliance with road laws - Allen, Siobhan (Policing and society, 2017)
Graduated driver licensing (GDL) is designed to reduce young driver injuries and fatalities on the road. While GDL systems impose additional restrictions on new drivers to reduce this crash risk, compliance with these restrictions and other licensing requirements can be low for young drivers. This research examines the influence of informal and formal deterrence measures on the compliance of provisionally licensed drivers, and the role that shame plays in mediating these relationships. The key independent variables measured were informal deterrence imparted by parents, formal deterrence imparted by police, and shame-related emotion, while compliance with road laws was the dependent variable. Using survey data from 151 young provisionally licensed drivers from Australia, the results indicate that informal deterrence, but not formal deterrence, is related to young drivers’ compliance with road rules. Further, the effect of informal deterrence on compliance behaviour was mediated by young drivers’ feelings of shame over wrong-doing. These findings suggest that internal psychological mechanisms need to be examined in addition to deterrence processes to understand young drivers’ compliance behaviour. Importantly, this study has key policy implications including the utilisation of third-party policing practices such as the inclusion of parents in monitoring young drivers’ behaviour on the road.